Associations between food security status and diet-related outcomes among students at a large, public Midwestern university - Leung, Cindy W. (J Acad Nutr Diet, 2019)
BACKGROUND: Food insecurity is a growing issue of concern on college campuses. While many studies have focused on predictors of food insecurity, fewer studies have examined how food insecurity affects diet and diet-related outcomes among college students. OBJECTIVE: The objectives of this study were to examine differences in dietary intake, food and cooking agency, and body mass index by food security status in a sample of college students at a large, public Midwestern university DESIGN: Cross-sectional online survey administered from March–June 2018. PARTICIPANTS: Students were recruited from a random sample (n=2,000) provided by the university, which included an oversample of minority racial/ethnic students, from lower-income households, and first-generation students. The response rate was 43% (n=851). After excluding students with missing data, the final sample was 754 enrolled students. MAIN OUTCOME MEASURES: Food security status was measured using the U.S. Adult Food Security Survey Module. Dietary intake was assessed using the National Cancer Institute dietary screener questionnaire. Cooking and food agency was measured using the Cooking and Food Provisioning Action Scale (CAFPAS), a new validated questionnaire. BMI was calculated from self-reported height and weight. STATISTICAL ANALYSIS PERFORMED: Differences between food security categories and diet-related outcomes were examined using generalized linear models. Models adjusted for sociodemographic covariates, such as student’s age, sex, race/ethnicity, and receipt of financial aid. RESULTS: Compared to students with high food security, low food security was associated with lower intake of fruits, and very low food security was associated with higher intakes of total added sugar and added sugar from sugar-sweetened beverages. Marginal and very low food security were positively associated with BMI. Marginal, low, and very low food security were inversely associated with cooking and food agency. CONCLUSION: Students with food insecurity experience diet-related challenges that could translate into health disparities over time. More research is needed to understand the longitudinal effects of food insecurity on student health and well-being.